Expression of cancer testis antigens in pancreatic carcinoma cell lines, pancreatic adenocarcinoma and chronic pancreatitis - Kubuschok, Boris; Xie, Xiaoxiun; Jesenofsky, Ralf; Preuss, Klaus-Dieter; Romeike, Bernd F.M.; Neumann, Frank; Regitz, Evi; Pistorius, Georg; Schilling, Martin; Scheunemann, Peter; Izbicki, Jakob R.; Löhr, J.-Matthias; et al. (International journal of cancer, 2004)
In order to define antigens that might be suitable as vaccines for pancreatic carcinoma, we investigated the composite expression of 10 cancer testis (CT) antigens (SCP-1, NY-ESO-1, SSX-1, SSX-2, SSX-4, GAGE, MAGE-3, MAGE-4, CT-7 and CT-8) by Reverse Transcriptase-PCR (RT-PCR) in fresh biopsies of human pancreatic adenocarcinoma, chronic pancreatitis and pancreatic carcinoma cell lines. While all CT genes were frequently expressed in cell lines derived from pancreatic cancer, no expression of MAGE-3, SSX-1, SSX-2, NY-ESO-1 and CT-7 was detected in fresh tumor biopsies, and MAGE-4 (1/52), SSX-4 (1/39) and CT-8 (2/41) were only rarely expressed. In contrast, HOM-TES-14/SCP-1 was expressed in 48% (29/61) and GAGE in 21% (13/61) of cases, respectively. One CT gene was expressed by 59% (75% in male, 46% in female patients; p = 0.05) and 2 or more CT genes by 15% of the samples. SCP-1 protein expression correlated well with mRNA expression. While SCP-1 and GAGE were absent in normal pancreas, they were found in 2/8 (SCP-1) and 1/8 (GAGE) samples of chronic pancreatitis, respectively, supporting the concept of chronic pancreatitis as a premalignant condition. SCP-1 and GAGE represent promising candidates for vaccine development in pancreatic carcinoma. Whether SCP-1 and GAGE expression identify cases of chronic pancreatitis with a high risk of malignant transformation remains to be shown. © 2004 Wiley-Liss, Inc.